From Outreach to Equity : Innovative Models of Library Policy and Practice. - Osborne, Robin (ALA Editions, 2004)
The many assumptions about current library outreach services - that they're off-site, depend on special funding, and are administered by specific staff - no longer reflect the realities of providing equitable library services to the audiences who most need them. This guide answers both "why" and "how."